(untitled) (Tanzania Medical Journal, 2023)
Background Children with Sickle Cell Disease (SCD) are prone to bacterial infections due to compromised immunity resulting in significant morbidity and mortality. Routine use of oral penicillin prophylaxis in patients with SCD and pneumococcal conjugate vaccine over the past three decades has led to a drastic decline in morbidity and mortality. However, there are reports of increasing antibiotic resistance globally, including penicillin. This study determined the proportion of bacteremia, antibiotic susceptibility patterns, and associated factors among febrile children with SCD. Method This was a hospital-based cross-sectional study conducted in Northwestern Tanzania between January and June 2021. A convenient sampling technique was used to select the study participants. The socio-demographic and clinical characteristics of the study participants were collected using a structured questionnaire upon obtaining consent from the parents/guardians. Blood samples for culture were collected aseptically before antibiotics use. Univariate and multivariable logistic regression analysis determined factors independently associated with bacteremia using odds ratios, 95% confidence intervals, and a p-value cut-off of < 0.05. Results The proportion of febrile children with bacteremia was 8.7% (28/321), predominately caused by S. aureus (64.3%) and K. pneumoniae (17.9%). The gram-positive isolates were more resistant to penicillin, erythromycin, and co-trimoxazole, with resistance rates ranging from 56 -78%. Gram-negative bacteria showed a high resistance rate (60-100 %) to ceftriaxone, amoxicillin-clavulanic acid, and cefepime. Children aged 0-5 years had twice the odds of having bacteremia (AOR=2.1, 95% CI=1.2-6.9) compared to children above five years, p =0.04. Furthermore, the odds of having bacteremia among males were 1.5 times (AOR=1.5, 95% CI=1.1-3.9) compared to females, p =0.03. Conclusion Our findings show that many children with SCD still acquire bacterial infection with S. aureus, constituting most bacteremic episodes. Additionally, we observed high resistance rates toward penicillin and other commonly used antibiotics. The high resistance rates call for introducing the routine culture and AST at health facilities that lack the services.